Defective utits determination of asynchronous motor during periodic diagnosis - Vovk, Oleksandr; Вовк, Олександр Юрійович; Вовк, Александр Юрьевич; Kurashkin, Serhii; Курашкін, Сергій Федорович; Курашкин, Сергей Федорович; Popova, Iryna; Попова, Ірина Олексіївна; Попова, Ирина Алексеевна (My University, 2019)
Research is dedicated the complex determination method to find out a current condition of asynchronous motor units, which are damaged during operation. The method is implemented using coefficients of the functional state of the motor units
Keywords: asynchronous motor; diagnosis; units damage; power loss; functional state coefficients